Review : APPLICATION OF FLIPBOOK TECHNOLOGY IN LEARNING AT SMK/SMA - I Gusti Kadek Surya Adnyana (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
In   recent   years,   flipbook   technology   has   emerged   as   an   interactive   digital   medium   in   education,   enhancing   the   learning   process.   Flipbooks   provide   a   print-like   reading   experience   enriched   with   digital   features   that   promote   interactivity   and   accessibility.   This   article   presents   a   systematic   literature   review   (SLR)   of   previous   studies   concerning   the   application   of   flipbook   technology   in   secondary   education,   particularly   in   vocational   and   general   high   schools.   The   review   examines   20   relevant   studies   to   understand   the   effectiveness,   challenges,   and   opportunities   associated   with   flipbook   implementation   in   education. Keywords:   flipbook,   digital   learning,   vocational   school,   high   school,   interactive   media,   systematic   literature   review